Ethnicity influences disease characteristics and symptom severity in allergic rhinitis patients in Malaysia - Amini, Peyman; Abdullah, Maha; Lee, Sing Seng; Karunakaran, Thanusha; Norzhafarina Hani; Abu Bakar, Saraiza; Abdul Latiff, Amir Hamzah; Seow, Heng Fong; Yap, Yoke Yeow (Wiley-Blackwell, 2014)
Background: The number of available reports regarding the influence of ethnicity on clinical features of allergic rhinitis (AR), especially disease severity in tropical climates, is limited. We aimed to compare clinical parameters and disease severity in AR patients of different ethnicities.